Myrcia lucasae (Myrtaceae), a new species from the campo rupestre of Chapada Diamantina, Brazil - Almeida, Roberto Baptista Pereira; Antar, Guilherme Medeiros; Vasconcelos, Thais; Santos, Leidiana L.; Amorim, Bruno S. (Phytotaxa, 2020)
Myrcia lucasae (Myrcia sect. Gomidesia, Myrtaceae), a new species from the Bahia state, Brazil, is here described and illustrated. It differs from M. lughadhae, a closely related and sympatric species, by the strigose indumentum with ferruginous trichomes and the absence of ribs on fruits. It is also different and from M. virgata (Myrcia sect. Myrcia), by presenting thecae with irregular dorsal openings (characteristics of Myrcia sect. Gomidesia). Collections of M. lucasae have been constantly misidentified as the morphologically similar M. virgata, a species from a different section, which does not occur in the state of Bahia. Myrcia lucasae is endemic to the highly diverse campo rupestre vegetation of the Chapada Diamantina biogeographic province. We also provide preliminary conservation assessment, comments on distribution and ecological aspects of this new taxon.